(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2026)
This article provides a theoretical and methodological analysis of the process of convergence between academic freedom and research activity within the context of the modern higher education system, particularly in an environment characterized by the rapid implementation of digital and artificial intelligence technologies. The pedagogical significance of academic freedom in fostering students’ scientific subjectivity, developing independent and critical thinking, and forming reflective research competencies is substantiated. Research activity is interpreted as an integral and systematic component of the educational process, supported by artificial intelligence–based digital tools, which ensures students’ intellectual development and the formation of scientific thinking. The research findings demonstrate that the integration and mutual alignment of academic freedom and scientific inquiry, including their integration with artificial intelligence technologies, play a crucial role in shaping an innovative and reflective pedagogical environment in higher education.